24/7 - Brown, Jim (Ballantine Books, 2001)
"Vassa Island has been rigged with remote control cameras, a surveillance satellite system, and the most powerful television transmitter ever created. And that's not all. For a small fee, anyone with a computer can access any of the 638 cameras live, twenty-four hours a day, seven days a week and vote as twelve carefully chosen contestants struggle with each other and the island." -- Jacket.
Keywords: Mother and child -- Fiction; Reality television programs -- Fiction; Sick children -- Fiction; Caribbean Area -- Fiction; Suspense fiction